القلق المعرفي وأثره في إسقاط الروايات الحديثية الصّحيحة - قريشي, مدحت (جامعة الوادي - University of Eloued, 2022)
لقد مارس الصّحابة رضوان الله عليهم عمليّة نقد التّراث فيما بينهم، واستندوا في ذلك إلى منهج ذي مسلكين: نقد التّراث بالاحتكام إلى العقل، ونقد التّراث بالاحتكام إلى النّقل. هذا المنهج الذّي أدّى ببعض الصّحابة رضوان الله عليهم إلى التّشكيك في رفع بعض الرّوايات الصّحيحة إلى النّبي صلى الله عليه وسلّم، بسبب ما تمّ الاصطلاح عليه في هذا البحث بالقلق المعرفي الذي يعتري تلك الرّوايات، تمامًا مثلما يفعل كثير من الباحثين اليوم. فهل للقلق المعرفي الذي يشوب بعض الروايات الصّحيحة أثر مهمّ في إسقاط النّصوص الحديثية الصحيحة، والتّشكيك في نسبتها إلى النّبي صلّى الله عليه وسلّم، وما مدى صحّة هذا المسلك ؟. وفي أثناء الإجابة على هذه الإشكالية، تهدف هذه الدراسة إلى كشف اللّثام عن الدّور الكبير الذي قام به الصّحابة في صيانة النّص الحديثي، ومحاولة وضع حدّ واضح لما تمّ الاصطلاح عليه في هذه الدّراسة بالقلق المعرفي، بالإضافة إلى محاولة المقاربة بين تصرّف بعض الصّحابة اتّجاه بعض الروايات الحديثية الصحيحة نقدًا وإسقاطًا، وتصرّف بعض الباحثين اليوم من نفس المنطلق. وقد وظّفنا في هذه الدّراسة المنهج التّحليلي النّقدي من أجل تحقيق ما تمّ تسطيره أعلاه. وبفضله تمّ التوصّل إلى جملة من النتائج، أهمّها أنّ الاتّجاه مباشرةً إلى ردّ الأحاديث الصّحيحة الّتي ثبتت بقواعد النّقد الحديثية المتينة علميّا، من منطلق القلق المعرفي؛ هو إجراء فيه تكلّف وإجحاف في حقّ النّصّ الحديثي، وممارسة تنمّ عن ضعف علميّ في حقّ الباحث، أو عن تسرّعٍ غير محمود في أحسن الأحوال. The Companions, may Allah have mercy on them, have tried to establish a process of criticism of the traditions among themselves and have relied on two ways : First, to criticize the tradition by resorting to reason, and second, to carry out this criticism by referring to the sacred texts (Al-Quran and authoritative Sunnah). This approach, which led some of the Companions, may Allah be pleased with them, to doubt the transmission of some authentic traditions to the Prophet, may Allah's prayer and peace be upon him, due to what has been referred to in this research as the cognitive anxiety that plagues these traditions, as many researchers do today. Does the cognitive anxiety have an important effect in dropping the authentic Hadith traditions and query its relation to the prophet and how valid is this approach?, While answering this problem, this study aims to show the role that the Companions played in maintaining the Hadith text and to try to put a clear end to what has been labeled cognitive anxiety in this study. In addition to trying to approach the behavior of some of the companions toward some authentic hadith narrations through criticism and omission, some researchers today have acted on the same premise. In order to achieve what has been described above, we have used the critical-analytical method in this study. Thanks to it, a number of results have been obtained, the most important of which is the direct tendency to respond to the correct hadiths, which have been proven under the criteria of scientific textual criticism of hadiths, out of cognitive fear. It is a procedure in which it is costly and unfair to the hadith text, and an exercise that indicates a scientific weakness in the right of the researcher, or at best an unwelcome haste.
Cognitive Anxiety And İts İmpact On Omission Of Authentic Hadith Narrations
مقال
Keywords: القلق المعرفي ; النّص الحديثي ; نقد التراث ; إسقاط الرواية ; التراث; Bilgelik kaygısı, hadis metni, İslam ilimleri mirasını tenkit, sahâbe, rivâyet reddi.